Argan Oil: Chemical Composition, Extraction Process, and Quality Control - Gharby, Said; Charrouf, Zoubida (Frontiers in Nutrition, 2022)
Argan oil is considered a relatively new international product exported only from Morocco, although different companies in Europe and North America distribute argan oil around the globe. Argan oil is a non-refined vegetable oil, of the more well‐known “virgin oil” type, is produced from the argan tree [Argania spinosa (L.) Skeels], a species endemic to Southwestern Morocco. The argan tree is deemed to be an important forest species from both social and economic standpoints. Argan oil has rapidly emerged as an important product able to bring more income to the local population. It also has important environmental implications, owing to its ability to stand against desert progression. Currently, Argan oil is mainly produced by women’s cooperatives in Morocco using a semi-industrial mechanical extraction process. This allows the production of high-quality argan oil. Depending on the method used to prepare argan kernels, two types of argan oil can be obtained: food or cosmetic grade. Cosmetic argan oil is prepared from unroasted kernels, whereas food argan oil is achieved by cold pressing kernels roasted for a few minutes. Previously, the same food argan oil was prepared exclusively by women according to a laborious ancestral process. Extraction technology has evolved to obtain high-quality argan oil at a large scale. The extraction process and several accompanying parameters can influence the quality, stability, and purity of argan oil. In view of this, the present chapter discusses different aspects related to argan oil chemical composition along with its nutritional and cosmetic values. Likewise, it details different processes used to prepare argan oil, as well as its quality control, oxidative stability, and authenticity assessment.